1957
DOI: 10.1111/j.1096-3642.1957.tb00286.x
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of Potamotherium an Oligocene Lutrine

Abstract: Summary. A detailed account is given of the anatomy of the skeleton and dentition of Potamotherium, the first known otter, from Upper Oligocene lacustrine deposits in Allier, central France. Almost all parts of the skeleton are represented: the bones are plentiful and well preserved, displaying many aquatic adaptations. The taxonomy of the Lutrinae, the stratigraphy of the deposits containing Potamotherium and their associated fauna are briefly discussed in the introduction. Study of the dentition includes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

1968
1968
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 10 publications
1
61
0
1
Order By: Relevance
“…Alligator mississippiensis, though semiaquatic, does not use its forelimbs to 'fly' underwater, or to paddle (Meers, 1999), which suggests that it does not need a comparably rigid elbow joint area. The observation that the radial and ulnar articulations with the humerus are not aligned in the plane of elbow joint flexion and extension, with one on top of the other, as in many other tetrapods with stiff elbow joints, supports this assumption (Martins, 1862;Alix, 1863;Alix, 1874;Hultkrantz, 1897;Parsons, 1899;Vialleton, 1924;Savage, 1957).…”
Section: Discussion Significant Treatment Observer and Species Intermentioning
confidence: 95%
“…Alligator mississippiensis, though semiaquatic, does not use its forelimbs to 'fly' underwater, or to paddle (Meers, 1999), which suggests that it does not need a comparably rigid elbow joint area. The observation that the radial and ulnar articulations with the humerus are not aligned in the plane of elbow joint flexion and extension, with one on top of the other, as in many other tetrapods with stiff elbow joints, supports this assumption (Martins, 1862;Alix, 1863;Alix, 1874;Hultkrantz, 1897;Parsons, 1899;Vialleton, 1924;Savage, 1957).…”
Section: Discussion Significant Treatment Observer and Species Intermentioning
confidence: 95%
“…The fossil collected from Chhorwali Katas by Gill provides support for this view, reflected in the decision to include Vishnuonyx in the Enhydriodontini. It does not refute an eventual relationship to Potamotherium (Pohle, 1919), the morphology of which could represent the grundplan from which other otters may have evolved (Savage, 1957) although this has been the subject of debate (De Muizon, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, many authors have included late Oligocene Potamotherium Geoffroy, 1833, in the Lutrinae (Matthew, 1929;Savage, 1957) but Willemsen (1992) discussed the question in depth and showed that this was far from being firmly established. Matthew (1929) considered that Enhydriodon was not a true lutrine, and that therefore it could not be closely related to Potamotherium which he did consider to be a lutrine.…”
Section: Origin Of the Enhydriodontinimentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ictonychines are either sister to or close to the base of the lutrines and thus we used Galictis as a second outgroup. In this context, we did not use Potamotherium as an outgroup, as it has been postulated to be an ancestral lutrine by several early studies (Thenius 1949b;Savage 1957;Fahlbusch 1967;Sokolov 1973;Willemsen 1992) but not by others (Muizon 1982). Whether Potamotherium is a musteloid or related to the origin of the pinnipeds (Rybczynski et al 2009), its phylogenetic position is considered too doubtful to include in an otter phylogeny.…”
Section: Methodsmentioning
confidence: 99%